Magnetic phase transitions in solid solutions of Fe-containing perovskite multiferroics. (4th April 2019) - Raevski, I. P.; Kubrin, S. P.; Pushkarev, A. V.; Olekhnovich, N. M.; Radyush, Y. V.; Li, G. R.; Chou, C.-C.; Raevskaya, S. I.; Titov, V. V.; Malitskaya, M. A.
Abstract: Concentration dependences of magnetic phase transitions temperatures TM for several solid solutions of perovskite multiferroics BiFeO3, PbFe1/2 Nb1/2 O3 (PFN), and PbFe0.5 Sb0.5 O3 (PFS) have been studied using Mössbauer spectroscopy. In all the solid solutions studied, the values of TM were found to depend not only on the concentration of the Fe 3+ ions in the lattice, but also on the short-range and/or long-range ordering of Fe 3+ and B 5+ ions, as well as on the mean lattice parameter values and on the nontrivial magnetic superexchange involving the empty p-orbitals of Pb 2+ and Bi 3+ cations.